The Electronic Payment System And Its Role In Strengthening The Financial Inclusion In Algeria: An Analytical Study - Ben Oudona Bouhafs; Morsli Naziha (جامعة الوادي University of Eloued, 2024)
The purpose of this study is to demonstrate how Algeria's financial inclusion has been strengthened by the use of electronic payment systems. In the process, we analyse Algeria's financial inclusion and the current state of the electronic payment system using the descriptive technique. Results indicate that via the expansion of banking services, Algeria's electronic payment systems have enhanced the financial inclusion indices in recent years. Additionally, as more people turn to credit cards instead of cash to make payments, the amount of money transacted via cards has grown owing to the efforts of banks and post offices. Ultimately, the study suggested that the infrastructure of ICTs be improved in order to enable banks and financial technology startups to conduct business using the electronic payment system. Furthermore, a national strategy to raise financial education and, consequently, financial, technical, and banking expertise must be established, and the experiences of the states that attained high levels of financial inclusion must be emulated
Keywords: Electronic payment systems; Financial inclusion; Financial technology; Financial services